EXPLORING THE IMPACT OF KAHOOT ON STUDENTS’ INTRINSIC AND EXTRINSIC IN ENGLISH LANGUAGE LEARNING: A WITHIN-SUBJECT STUDY OF EIGHTH-GRADE STUDENTS - Rahmawati, Norliana; Sunarti, Sunarti; Rahmawati, Yeni; Khatimah, Khusnul; Puspita, Rani Herning (Jurnal Visipena, 2025)
This study aims examines the Role of Kahoot in enhancing students’ motivation in English Learning This study employed a within-subject design and involving 16 eighth-grade students from SMP Muhammadiyah 1 Samarinda, who experience both conventional instruction and Kahoot-based instruction. This instrument used in this research was test and questionnaire to collect the data. The results showed a significant increase in student motivation following the use of Kahoot, with higher post-test scores and more consistent performance. Notably, students with lower initial motivation exhibited the greatest improvement, indicating Kahoot’s potential to support less motivated learners. Overall, the study found that Kahoot fosters a more interactive, enjoyable, and engaging learning environment, thereby enhancing students’ motivation and learning outcomes in English language education.